The Effect of Work Discipline and Work Motivation on Employee Performance At PT Perkasa Beton Batam - Betharia Claudina Situmorang; Mauli Siagian (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
This study aims to determine the effect of work discipline, work motivation on employee performance at PT Perkasa Beton Batam either partially or simultaneously. The population in this study were employees with operator positions and office in all department with a total of 112 employees. The number of samples taken for this study were 112 respondents. The sampling technique in this study was carried out by means of the saturated sample technique. Data collection techniques in this study is used a questionnaire. This data is processed using SPSS version 26.0 software. The research method used is quantitative method. The results showed that work discipline had a positive and significant effect on employee performance at PT Perkasa Beton Batam with t value of 10.113 > t table 1.981967, and work motivation had a positive and significant effect on employee performance at PT Perkasa Beton Batam with at value of 3.679 > t table 1.981967. The results of the study also prove that work discipline and work motivation simultaneously affect employee performance at PT Perkasa Beton Batam, with a calculated f value of 498,847 > f table 3,08.